Crisis Communication Management amid Bond Market Volatility in Vietnam (2021–2024) - Nguyen, Khuyen Thi; Nguyen, Toan Duc; Tran, Minh Ngoc Thi (International Journal of Humanities, Education, and Social Sciences, 2025)
The bond market in Vietnam experienced significant turbulence between 2021 and 2024, driven by macroeconomic shocks, regulatory transitions, and notable financial scandals. This period exposed vulnerabilities in market oversight, investor confidence, and information dissemination channels. Effective crisis communication emerged as a pivotal tool for mitigating the adverse effects of market instability and preserving financial system integrity. This article examines how Vietnamese government agencies, financial institutions, and media outlets managed crisis communication during episodes of bond market volatility in this period. Using qualitative content analysis of official statements, media reports, social media discourse, and investor sentiment surveys, this study identifies communication strategies, evaluates their efficacy, and highlights lessons for future crisis preparedness. Findings emphasize transparency, timeliness, message coordination, and multi-channel engagement as key factors in successful crisis communication. The paper concludes with recommendations for strengthening Vietnam’s crisis communication frameworks tailored to the evolving financial and media landscapes.